2021
DOI: 10.1177/0094582x211020748
|View full text |Cite
|
Sign up to set email alerts
|

Decolonizing Our Feminist/ized Revolutions: Enfleshed Praxis from Southwest Colombia

Abstract: An initial mapping of the decolonial feminisms emergent in Buenaventura and Cali, Southwest Colombia, in the Afro-Colombian and indigenous political Escuela de Mariposas de Alas Nuevas and Círculo de Hombres, Cali, shows that they move within and beyond a politics and epistemology of representation in a return to the enfleshed as territories of transformatory wisdoms and the embrace of ancestrality and feminist spirituality. Un mapeo inicial de los feminismos decoloniales surgidos en Buenaventura y Cali, en e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This experience, that I call Magical Saudade , made emerge the three mothers that are in me: La Virgen de Guadalupe, La Malinche and la Llorona. This opened the gates to engage with a colonial past (Galván, 2014; Motta, 2021) to understand the complexities of these mothers in me (Anzaldúa, 1987; Matalobos, 2007; Perez, 2008). The magical feminism in my narrative refers then to apparently impossible events where I evoke symbolic imaginaries and where the three mothers physically appear to me.…”
Section: Magical Embodiment In Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This experience, that I call Magical Saudade , made emerge the three mothers that are in me: La Virgen de Guadalupe, La Malinche and la Llorona. This opened the gates to engage with a colonial past (Galván, 2014; Motta, 2021) to understand the complexities of these mothers in me (Anzaldúa, 1987; Matalobos, 2007; Perez, 2008). The magical feminism in my narrative refers then to apparently impossible events where I evoke symbolic imaginaries and where the three mothers physically appear to me.…”
Section: Magical Embodiment In Methodsmentioning
confidence: 99%
“…In this disenchantment, Western thinking (Galván, 2014; Santos, 2016) has displaced tradition, myth, and superstition (Suddaby et al., 2017) into categories of thought that are perceived as deficient (Berenstain et al., 2022) to build academic knowledge. But at the same time, our Western focus (Berenstain et al., 2022; Galván, 2014; Santos, 2016; Motta, 2021) on what is considered as valuable knowledge production at least partially explains our collective failure to imagine new possibilities (Fotaki et al., 2020; Islam & Greenwood, 2021) in answering on‐going world‐wide crises where some bodies are much more subjected to violence than others (Butler, 2009). Feminist scholars (Lorde, 2017; hooks, 1989; Anzaldúa, 1987; Anzaldúa, 1990; Butler, 2016; Ahmed, 2017; Dorlin, 2017) have powerfully shown that women's bodies fall into this category, that violence against women is epidemic (Wilcox et al., 2021), has no “ fronteras ” 2 (Londoño Toro et al., 2017) and that yes, there is a guerra “en” y “contra” el cuerpo de la mujeres 3 (Gago, 2019, p. 65).…”
Section: Re‐enchanting Our Writingmentioning
confidence: 99%
See 1 more Smart Citation
“…Crucially, the drawing of these hierarchical binaries and colonial/modern borders place the gendered and racialised as synonymous with emotionality as opposed to reason, flesh as opposed to modern subjecthood, and nature and conversative tradition as opposed to science and forward-moving progress. The former of the binaries is associated with the irrational, the unruly and the shameful – to be controlled and tamed with the building of the urban frontier and the lettered city to avoid disruption to the ‘normal' and ‘rational' social and physical order (Anzaldúa, 2007: 38–40; Lorde, 2000: 1–4; Motta, 2018, 2021). As Anzaldúa (2002: 541) explains:This system and its hierarchies impact people’s lives in concrete and devasting ways and justify a sliding scale of human worth used to keep humankind divided.…”
Section: Entering the Roots: Onto-epistemological Negation And Surviv...mentioning
confidence: 99%
“…Here that which has been rendered flesh and less-than-human relegated to non-being and epistemological terra nullius becomes a site/sites of knowing-being, relating and weaving the world otherwise. Re-connection to embodied memories of violation and suvivance when kneaded together through pedagogical praxis of popular and Indigenous education can create narratives which disrupt hegemonic discourses (as representations and material practise) that seek to name, shame, individualise and disarticulate (see Motta, 2018Motta, , 2021, for further discussion). Such reconnection and decolonising/feminised pedagogical praxis arguably offer medicinal epistemological-political practices across the body politic as the logics of disposability and anti-life survival of the fittest generalise across and fracture the certainties of knowing-being of the territories and bodies of the (anti)life of Whiteness.…”
Section: Mangrovesmentioning
confidence: 99%